KETERKAITAN KAJIAN BUDAYA DAN STUDI SASTRA DI INGGRIS: SEBUAH TELAAH SINGKAT - Muh Arif Rokhman (Humaniora, 2008)
The paper attempts to demonstrate the interrelationship between literary theory and criticism and Cultural Studies existing in the United Kingdom from 1920s to 1990s. The Liberal Humanism critical movement appearing around 1920s was the effect of the view of culture commonly shared by some intellectuals in the country. They believed that culture belonged to the smaller group of people in a higher social class. The more elite conception of culture was then responded by other groups of intellectuals belonging to the tradition of the Left. The latter held that culture included all activities of people in society regardless of their social class, a notion proposed by the proponents of British Cultural Studies. This then gave birth to another model of criticism called Cultural Materialism. From the discussion, it can be shown that literary criticism and cultural studies in UK during the era were strongly interrelated